Agensifikasi Pengelolaan Dana Bergulir: Studi Kasus pada Badan Layanan Umum Pengelola Dana Bergulir Tahun 2009-2013 - Wijaya, Nararia Sanggrama; Waluyo, Budi (JURNAL INFO ARTHA, 2015)
Agencification is widely usedasa kind ofpublic service reform aimed to achieving good governance. This concept is conducted in Indonesia through the implementation of Financial Management Pattern on Public Service Agency.This model emphasizes the applicationof financial flexibility, the principles of productivity, efficiency, and effectiveness. Several public service agencies implement it including fund management units. In this sector, the government has required the implementation of Financial Management Pattern Public Service Agency for government fund management units, especially for those a management of revolving fund.The purpose of this study isto describe a thorough and deep understanding around the agencification of five revolving fund management units and related factors influencing the distribution of this fund, from 2009 to 2013. It uses a quantitative approach to obtain sufficient evidence of those matters. Data and information obtained through study of documentation and a number of interviews. Furthermore, the data were analyzedusing Logical Framework Approach models.The analysis shows that the implementation of agencification for revolving fund in five revolving fund management units varies. This is in accordance with the characteristics, duties, and functions of each unit. The actual distribution of funds of those units is also diverse. P2H Center, the Government Investment Agency, as well as the Secretariat BPJT Funding Division has a poor distribution level, while the Centerfor Housing and LPDB KUMKM have a pretty good one.Low levels of revolving funds caused by several factors, including budgeting, regulation, credit risk, the external factors, and limitations of human resources.